A comparative study on parental rearing styles and competitive attitudes among college students from different family income backgrounds - Zhou, Shuqing; Wang, Dong; Xu, Tingting (Frontiers in Psychology, 2025)
ObjectiveTo explore the differences in parental rearing styles and competitive attitudes between college students from low-income and non-low-income families. The goal is to provide insights into their holistic development and psychological adaptation in diverse competitive environments.MethodsA total of 1,000 college students were surveyed using a general information questionnaire, the Egna Minnen Beträffande Uppfostran questionnaire, and the Competitive Attitude Scale. Among them, 188 were identified as low-income students and 750 as non-low-income students.Results(1) Significant differences were observed between low-income and non-low-income students in parental emotional warmth and understanding, paternal denial and rejection, maternal favoritism, and malignant competitive attitude (p < 0.05). (2) Parental emotional warmth and understanding were positively correlated with benign competitive attitude (p < 0.01). (3) Parental rejection, denial, favoritism, and overprotection were negatively correlated with malignant competitive attitude (p < 0.05). (4) Paternal punishment and strictness were positively correlated with malignant competitive attitude (p < 0.01).ConclusionPositive parental rearing styles enhance the subjective well-being of low-income students and foster benign competitive attitudes, whereas negative parental rearing styles reduce well-being and promote excessive competitive tendencies.